Komunikasi Personal Selling pada Pemasaran Kerupuk Sidoarjo di Kolaka Sulawesi Tenggara - Dahlia Dahlia; Hadiati Hadiati; Abdul Samad (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This study aims to determine how much the role of personal selling in improving marketing performance in the midst of increasingly fierce competition in the Sidoarjo cracker industry marketing in Kolaka, Southeast Sulawesi. In this research, the method used is descriptive qualitative. With data collection techniques, namely: interview, observation, questionnaire and documentation. The data obtained were analyzed descriptively with data reduction, data presentation and conclusion drawing. The results found that employees at the Sidoarjo cracker distributor company in Kolaka have excellent perosnal selling communication competencies. They are able to convey and explain products clearly, offer products to customers with the right approach, and demonstrate active listening skills to customer complaints and needs. In addition, they are also proficient in responding to customer queries and complaints in a professional manner. Employees are also able to maintain effective communication during the sales process, which in turn makes potential buyers feel confident to buy the products offered. On the other hand, there are barriers in personal selling communication in Sidoarjo crackers marketing in Kolaka, Southeast Sulawesi, namely lack of product knowledge, cultural and language differences, resistance to new products, competition with local products, negative views of consumers who consider personal selling as a nuisance, and higher operational costs compared to other marketing methods.